Compositional Differences in the Oral Microbiome of E-cigarette Users - Chopyk, Jessica; Bojanowski, Christine M.; Shin, John; Moshensky, Alex; Fuentes, Ana Lucia; Bonde, Saniya S.; Chuki, Dagni; Pride, David T.; Crotty Alexander, Laura E. (Frontiers in Microbiology, 2021)
Electronic (e)-cigarettes have been advocated as a safer alternative to conventional tobacco cigarettes. However, there is a paucity of data regarding the impact of e-cigarette aerosol deposition on the human oral microbiome, a key component in human health and disease. We aimed to fill this knowledge gap through a comparative analysis of the microbial community profiles from e-cigarette users and healthy controls [non-smokers/non-vapers (NSNV)]. Moreover, we sought to determine whether e-cigarette aerosol exposure from vaping induces persistent changes in the oral microbiome. To accomplish this, salivary and buccal mucosa samples were collected from e-cigarette users and NSNV controls, with additional oral samples collected from e-cigarette users after 2 weeks of decreased use. Total DNA was extracted from all samples and subjected to PCR amplification and sequencing of the V3-V4 hypervariable regions of the 16S rRNA gene. Our analysis revealed several prominent differences associated with vaping, specific to the sample type (i.e., saliva and buccal). In the saliva, e-cigarette users had a significantly higher alpha diversity, observed operational taxonomic units (OTUs) and Faith’s phylogenetic diversity (PD) compared to NSNV controls, which declined with decreased vaping. The buccal mucosa swab samples were marked by a significant shift in beta diversity between e-cigarette users and NSNV controls. There were also significant differences in the relative abundance of several bacterial taxa, with a significant increase in Veillonella and Haemophilus in e-cigarette users. In addition, nasal swabs demonstrated a trend toward higher colonization rates with Staphylococcus aureus in e-cigarette users relative to controls (19 vs. 7.1%; p = n.s.). Overall, these data reveal several notable differences in the oral bacterial community composition and diversity in e-cigarette users as compared to NSNV controls.